Saúde bucal de povos e comunidades tradicionais do Brasil : revisão de escopo e inquérito epidemiológico em território quilombola na cidade de João Pessoa-PB - Raymundo, Maria Letícia Barbosa (2023)
Traditional Peoples and Communities (PCT) in Brazil are affected by health inequities, including oral health. Gathering epidemiological information about the oral health status is the initial step in making the epidemiological situation visible. The objective of this dissertation was to elucidate the health condition of PCT, and for this purpose, two work plans were developed. The first work plan involved designing and developing a scoping review protocol with the aim of mapping the available evidence on oral health research among Traditional Peoples and Communities (PCT) in Brazil through primary studies, addressing the following question: "What evidence is available regarding oral health surveys of Traditional Peoples and Communities in Brazil?". The scoping review was conducted following the Problem, Concept, and Context strategy, as established by the Joanna Briggs Institute. The search strategy included Medical Subject Headings terms, synonyms, and relevant free terms related to epidemiological surveys on oral health and PCT in Brazil, across the MEDLINE/PubMed, LILACS, Scopus, Web of Science, and Embase databases. The bibliographic searches were updated until July 2023. In the first stage of the study selection process, a total of 401 citations were found. Among these 401 studies, 211 were removed due to duplication. Based on the title, abstract, and keywords, 136 studies were excluded because they reported secondary data or were non-specific and non-representative of PCT. In the second selection stage, 61 studies were read in full, and 39 were included in the review. Two studies were manually added. The included studies were published between 1968 and 2023. Of these, 31 studies investigated the oral health condition of indigenous peoples, 7 were about quilombola communities, and 3 were about riverine peoples. No studies about Romani communities were found in the search. All studies were cross-sectional in nature, with the majority located in the Northeast region of the country (n=12), assessing dental caries as the primary oral health issue (n=13) through clinical examinations (n=25), with a high prevalence observed among PCT (n=11). The review conducted reveals that in Brazil, studies on the oral health of PCT are ongoing, albeit in an isolated and independent manner, indicating a considerably high prevalence of oral health problems in these communities. In the second work plan, a population-based cross-sectional epidemiological survey was conducted in a quilombola territory in the municipality of João Pessoa, Paraíba, with children aged 4 to 8 years. The objective was to assess the prevalence of dental caries through intraoral examinations and its associated factors, including sociodemographic and socioeconomic factors and nutritional factors measured through the cariogenic potential of the diet. The ceo-s (decayed, extracted, filled surfaces) and CPO-S (decayed, missing due to caries, filled surfaces) indices were used, along with the pufa/PUFA index, which quantifies the prevalence and severity of untreated dental caries-related oral conditions. Examinations were conducted on 146 children in the quilombola territory. Among the families who participated in the study, only 46.3% (n=62) self-identified as quilombolas. Regarding skin color, 63.2% (79) of the children were of mixed race. In terms of socioeconomic status, 69.7% (n=83) had income below the minimum wage, 67.4% (n=95) received government assistance, and the average household size was 4 (±1.38) individuals. In the Poisson multilevel regression model, using age, sex and receipt of assistance benefits as clusters, factors associated with the experience of dental caries, prevalence of untreated caries and the PUFA index were verified. Children from quilombola families declared non-white have a 5.69 times higher prevalence of experiencing tooth decay (PR =5.69, 95%CI 3.2 to 10.11). Those from quilombola families who have a cariogenic diet have a 1.84 times higher prevalence of cavities (PR=1.84, 95%CI 1.04 to 3.26). Therefore, children from quilombola, non-white families and those with a cariogenic diet have a higher prevalence of experiencing tooth decay, highlighting the influence of social factors and their intersectionalities on oral health. Furthermore, more studies on quilombolas are needed to bring visibility to this group.